Spacer‐Engineered Ionic Channels in Covalent Organic Framework Membranes toward Ultrafast Proton Transport. Issue 16 (6th March 2023) - Shi, Benbing; Pang, Xiao; Lyu, Bohui; Wu, Hong; Shen, Jianliang; Guan, Jingyuan; Wang, Xiaoyao; Fan, Chunyang; Cao, Li; Zhu, Tianhao; Kong, Yan; Liu, Yawei; et al.
Abstract: Side‐chain engineering of covalent organic frameworks as advanced ion conductors is a critical issue to be explored. Herein, ionic covalent organic framework membranes (iCOFMs) with spacer‐engineered ionic channel are de novo designed and prepared. The ionic channels are decorated with side chains comprising spacers having different carbon chain lengths and the –SO3 H groups at the end. Attributed to the synergistic contribution from the spacers and the –SO3 H groups, the iCOFM with moderate‐length spacer exhibit the highest through‐plane proton conductivity of 889 mS cm ‐1 at 90 °C. Abstract : The ionic covalent organic framework with moderate‐length spacer exhibits the highest through‐plane proton conductivity attributed to the synergistic contribution from the spacers and the –SO3 H groups.